Logic and theism : arguments for and against beliefs in God - Sobel, Jordan Howard (Cambridge University Press, 2004)
This is a wide-ranging book about arguments for and against beliefs in God. This book will be a valuable resource for philosophers of religion and theologians and will interest logicians and mathematicians as well.